Dynamics of food sources, ecotypic distribution and Trypanosoma cruzi infection in Triatoma brasiliensis from the northeast of Brazil. - Maurício Lilioso; Carolina Reigada; Dayane Pires-Silva; Fernanda von H M Fontes; Cleanne Limeira; Jackeline Monsalve-Lara; Elaine Folly-Ramos; Myriam Harry; Jane Costa; Carlos Eduardo Almeida (Public Library of Science (PLoS), 2020)
Innovative approaches used to combat Chagas disease transmission tend to combine a set of comprehensive efforts to understand the ecology of local vectors. In this work we identified molecularly the blood meal of 181 Triatoma brasiliensis, distributed in 18 populations (8 sylvatic and 10 peridomestic), which were collected across a range of 240 km (East-West) and 95 km (North-South) in the semi-arid region of northeastern, Brazil. We used the vertebrate mitochondrial gene (cytochrome B) sequencing applied to DNA isolated from bug midgut to identify the insect blood meal sources via the BLAST procedure. The peridomestic populations were classified according to two main hypotheses of site-occupancy for T. brasiliensis: the first says that the infestation is mainly driven by structures that resemble its natural habitat (stony-like ecotopes) and the second assumes that it is associated with key-hosts (rodents and goats). Rodents of the Caviidae family (Galea spixii and Kerodon rupestris) were identified as the key-host of T. brasiliensis, but also the potential Trypanosoma cruzi reservoir-able to connect the sylvatic and domestic T. cruzi cycle. Cats also deserve to be studied better, as potential T. cruzi reservoirs. By modeling the food sources + site-occupancy + T. cruzi natural infection, we identified man-made ecotopes suitable for forming dense triatomine infestations with high rates of T. cruzi natural infection, which may be taken into account for vector control measures.